HAEMAGLUTINATION OF Shigella flexneri SUBUNIT PILI PROTEIN 18 KDA AS A MOLECULE ADHESION IN MICE ENTEROCYTES - Fitrianingsih, Avin Ainur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Diarrhoeal diseases are still a major cause of the high morbidity and mortality of children globally, especially in children under five years. Diarrhea caused by Shigella flexneri usual dealt with antibiotics seen it is getting resistant with various antibiotic. Prevention shigellosis with a vaccine that was developed and used now are still limited. This study attempts to explore hemaglutinin protein pili S . flexneri allegedly role in adhesion bacteria on the mice enterocyte. This research using hemaglutination test then adhesion test by means of reacting protein sub unit pili 18 kDa S. flexneri with mice enterocyte cells and observed the amount of bacteria inherent in a mice cell enterocyte. The research found that proteins sub unit pili with molecules weight 18 kDa is a protein that capable to agglutinate mice red blood cells with highest dilution and capable to inhibit adhesion bacteria on the mice enterocyte significantly. Keywords: Shigella flexneri, protein sub unit pili , hemagglutinin protein, adhesin protein.